International environmental law policy and ethics - Gillespie, Alexander (Clarendon Press,Oxford University Press, 1997)
This innovative study shows how nations, like individuals, are creating environmental laws and policies that are continually inviting failure since such laws are riddled with inconsistencies and are ultimately contradictory in purpose